Green Innovation: Use of Residual Biomass in the Removal of Copper and Iron from Artisanal Mining Effluents - Quispe Banda, Daymaris Yesenia; Rojas Atilano, Gissel Yadeli; Licapa-Redolfo, Gladys S. (LACCEI, 2024)
This research aims to evaluate the influence of contact time and the proportion of Zuro Zea Mays and Musa Paradisiaca peel on the removal of copper and total iron from artisanal mining effluents. These emerging technologies stand out for their low cost and high efficiency in metal adsorption due to their physical and chemical properties. Firstly, the in-situ parameters of the artisanal mining effluent were characterized, obtaining an initial pH of 2.17, characteristic of a very acidic industrial effluent, with concentrations of copper of 532,900 mg/L and iron of 989,700 mg/L. Then, three treatments were carried out with doses of 10, 15 and 20g of Zuro de Zea Mays and Musa Paradisiaca peel and their respective repetitions. It was possible to identify that the optimal contact time for the removal of Fe and Cu was 6 hours, showing the best results in all treatments. For copper, concentrations of 434.9 mg/L, 366.086 mg/L and 164.163 mg/L were obtained, corresponding to 18.39%, 31.30% and 69.19% removal respectively. In the case of iron, the removal percentages were 42.16%, 63.26% and 78.21%, which also represents significant removals. It is concluded that these results suggest the viability of using complementary treatments to reduce the concentration of metals in industrial effluents from artisanal mining to achieve better results and make them an economically attractive proposal due to their accessibility.